2019
DOI: 10.1021/acssensors.9b00440
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Food Packaging: A Review of Smart Sensing Technologies for Monitoring Food Quality

Abstract: Food safety is a major factor affecting public health and the well-being of society. A possible solution to control food-borne illnesses is through real-time monitoring of the food quality throughout the food supply chain. The development of emerging technologies, such as active and intelligent packaging, has been greatly accelerated in recent years, with a focus on informing consumers about food quality. Advances in the fields of sensors and biosensors has enabled the development of new materials, devices, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
234
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(268 citation statements)
references
References 127 publications
1
234
0
3
Order By: Relevance
“…Intelligent packaging has been a major research topic in the food industry and many of its technologies can also be applied in pharmaceutical packaging. The literature review suggests that the main purpose for intelligent food packaging focuses on monitoring the freshness of the food content rather than observing the storage condition of the medicines in pharmaceutical packaging [40]. Deterioration of the packaged food is basically the major concern in the food industry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intelligent packaging has been a major research topic in the food industry and many of its technologies can also be applied in pharmaceutical packaging. The literature review suggests that the main purpose for intelligent food packaging focuses on monitoring the freshness of the food content rather than observing the storage condition of the medicines in pharmaceutical packaging [40]. Deterioration of the packaged food is basically the major concern in the food industry.…”
Section: Resultsmentioning
confidence: 99%
“…Application of technologies to these concepts, especially the environmental condition monitoring, is closely resembled to the pharmaceutical counterpart where the sensors are measuring the surroundings of pharmaceutical packaging rather than the space inside food packaging. Sensing technologies based on chemical, biological or physical sensors are the core components in intelligent food packaging enabling passive or active indications of the status of the packaged food to consumers [40,41]. Collection of articles was first focused on technologies applying directly to pharmaceutical packaging, but those that applied to food packaging were also chosen in this study when no relevant article was found in the pharmaceutical sector.…”
Section: Resultsmentioning
confidence: 99%
“…However, modern technology and materials science have introduced new "smart" functions to food packages, which include advanced packaging materials with improved properties, and sensors that can monitor food quality (Yam et al, 2005;Kuswandi et al, 2011). Over the years, several approaches toward smart packaging have been demonstrated including time-temperature indicators, modified atmosphere packaging sensors for CO 2 and O 2 monitoring, total volatile base nitrogen sensors to detect food decay, fruit ripeness indicators, pathogen sensors, and solutions for food tracking and authentication (RFID tags) (Fuertes et al, 2016;Ghaani et al, 2016;Ahmed et al, 2018;Badia-Melis et al, 2018;Galstyan et al, 2018;Mustafa and Andreescu, 2018;Yousefi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sensors are being developed for every possible aspect of modern life, ranging from the detection of air pollutants [1] and food contaminants [2], monitoring health biomarkers [3,4], and even assisting in the detection of extra-terrestrial life [5]. There are many characteristics of an effective sensor, including high sensitivity, selectivity, high signal-to-noise ratio, fast response time, and reliability/stability.…”
Section: Introductionmentioning
confidence: 99%